Ecology And Habitat Characteristics Of The Yellow-Crested Cockatoo (Shulpurea cockatoo) In The Tanjung Pasir Area, Taman Buru, Moyo Island, Indonesia - Muhammad Yul Fikry; Kayla Al Khansa Munthe; Dzar Al Ghifari; Muhammad Abdul Rokhim; Hafizh Haritsah (Ecobios Journal Of Environmental Science, 2024)
This study examines the habitat and ecological characteristics of the Yellow-crested Little Cockatoo (Cacatua sulphurea) on Moyo Island, West Nusa Tenggara, to identify the types of trees used as habitats and conditions that affect the existence of the population. Data were collected through direct observation, in-depth interviews, and measurements of tree characteristics. The results of the study showed that this bird perches on Binong (Alstonia angustiloba) and Asam (Tamarindus indica) trees, with a preference for large-diameter trees and irregular crowns. Trees with a diameter of 53 cm to 220 cm and a height of 4 to 23 meters above ground level have proven to be an ideal perch for the yellow-crested cockatoo (Cacatua sulphurea).The large diameter of the tree provides a large surface for perching, while the sufficient height allows the bird to have a wider view of the surrounding environment. This suggests that the choice of a perch by a cockatoo is influenced not only by the size of the tree, but also by the ecological function offered by the tree. However, this bird population is threatened by habitat destruction due to forest encroachment and land conflicts. This study provides important insights into the habitat conservation of the Yellow-crested Little Cockatoo and emphasizes the need for more intensive conservation efforts to protect this species from extinction and maintain the balance of the Moyo Island forest ecosystem.